Apocrine carcinomas of the breast in Turkish women: Hormone receptors, c-erbB-2 and p53 immunoexpression - KAYA, HANDAN; ERBARUT SEVEN, İPEK; BOZKURT, SÜHEYLA (ELSEVIER GMBH, 2008)
The aims of this study were twofold: (i) to determine the occurrence frequency of apocrine carcinoma of the breast (ApBCa) in Turkish breast cancer (BCa) patients; and (ii) to evaluate the expression of estrogen receptor (ER), progesterone receptor (PR), androgen receptor (AR), gross cystic disease protein-15 (GCDFP-15), c-erbB-2, and p53 in these cases. Six hundred and twenty-six cases of BCa were studied immunohistochemically (streptoavidin-biotin horseradish peroxidase method). The results of ApBCa were compared with those of invasive ductal carcinoma not otherwise specified type (IDC-NOS) cases of similar grade. Thirteen cases of ApBCa were encountered, accounting for 2.1% of all BCa cases. Immunohistochemically, ApBCa positivity was as follows: GCDFP-15 (100%), ER (39%), PR (8%), AR (54%), p53 (39%), and c-erbB-2 (85%). In the IDC-NOS group, GCDFP-15* was expressed in less than 50% of the tumors. The occurrence frequencies of the other markers were as follows: ER (69%), PR (69%)*, AR (46%), c-erbB-2 (0%)*, and p53 (31%), (*) indicating significant differences between the two groups. For Turkish BCa patients, (i) the occurrence rate of ApBCa (2.1%) was high; and (ii) the following combination would allow for an immunohistochemical identification of ApBCa: GCDFP-15(+), c-erbB-2(+), and PR-. (C) 2008 Elsevier GmbH. All rights reserved.
Keywords: apocrine carcinoma; breast; hormone receptor; oncogene; PROGESTERONE-RECEPTOR; ESTROGEN-RECEPTOR; IMMUNOHISTOCHEMICAL ANALYSIS; ANDROGEN RECEPTORS; EXPRESSION; MUTATIONS; FREQUENCY; PATHOLOGY; CANCER; AGE